Competence of health care providers on care of newborns at birth in a level-1 health facility in Yaoundé, Cameroon - Monebenimp, Francisca (The African Field Epidemiology Network, 2012)
INTRODUCTION: This is an observational study which was carried out at a level one health facility in Yaoundé from June to July 2009. The aim was to evaluate the competence of health care providers towards newborns’ care at birth METHODS: Ten health care providers took care of three hundred and thirty-five pregnant women who were enrolled for the study after informed verbal consent in the delivery room. RESULTS: Out of 340 offspring delivered and taken care of, 179 (52.6%) were male and 161 (47.4%) were female. Only two out of ten health workers had a WHO Essential Newborn Care (ENC) training. None of them had received any refresher course for the past two years. The mean gestational age of women was 39.5±3.5 weeks. Resuscitation was carried out on 21 (6.2%) of the newborns including 7 (33.3%) who had birth asphyxia. Health care providers scored 100% in performing the following tasks: warming up the baby, applying eye drops, injecting vitamin K, identifying the neonate, searching for any apparent life threatening congenital malformations, preventing for infection after procedures and initiating breastfeeding. The score was 24% at neonatal resuscitation tasks. Low level of education was associated with poor competence on applying ENC tasks (p<0.001). Lack of WHO ENC training was associated with poor competence on ENC tasks (p<0.001) and poor skills on resuscitation (p=0.03). CONCLUSION: There is a need to reinforce the capacity of health care providers by training in WHO ENC course with emphasis on providing skills on resuscitation in order to reduce the burden of neonatal intrapartum-related deaths.